Tumor dosimetry using [(124)I]m-iodobenzylguanidine microPET/CT for [(131)I]m- iodobenzylguanidine treatment of neuroblastoma in a murine xenograft model - Seo, Youngho (2012)
PURPOSE: [(124)I]m-iodobenzylguanidine ((124)I-mIBG) provides a quantitative tool for pretherapy tumor imaging and dosimetry when performed before [(131)I]m-iodobenzylguanidine ((131)I-mIBG) targeted radionuclide therapy of neuroblastoma. (124)I (T(1/2)=4.2d) has a comparable half-life to that of (131)I (T(1/2)=8.02d), and can be imaged by PET for accurate quantification of the radiotracer distribution. We estimated expected radiation dose in tumors from (131)I-mIBG therapy using (124)I-mIBG microPET/CT imaging data in a murine xenograft model of neuroblastoma transduced to express high levels of the human norepinephrine transporter (hNET). PROCEDURES: In order to enhance mIBG uptake for in vivo imaging and therapy, NB 1691-luciferase (NB1691) human neuroblastoma cells were engineered to express high levels of hNET protein by lentiviral transduction (NB1691-hNET). Both NB1691 and NB1691-hNET cells were implanted subcutaneously and into renal capsules in athymic mice. (124)I-mIBG (4.2–6.5 MBq) was administered intravenously for microPET/CT imaging at 5 time points over 95 hours (0.5, 3–5, 24, 48, and 93–95 h median time points). In vivo biodistribution data in normal organs, tumors, and whole-body were collected from reconstructed PET images corrected for photon attenuation using the CT-based attenuation map. Organ and tumor dosimetry were determined for (124)I-mIBG. Dose estimates for (131)I-mIBG were made, assuming the same in vivo biodistribution as (124)I-mIBG. RESULTS: All NB1691-hNET tumors had significant uptake and retention of (124)I-mIBG, whereas unmodified NB1691 tumors did not demonstrate quantifiable mIBG uptake in vivo, despite in vitro uptake. (124)I-mIBG with microPET/CT provided an accurate 3-dimensional tool for estimating the radiation dose that would be delivered with (131)I-mIBG therapy. For example, in our model system, we estimated that the administration of (131)I-mIBG in the range of 52.8 – 206 MBq would deliver 20 Gy to tumors. CONCLUSION: The overexpression of hNET was found to be critical for (124)I-mIBG uptake and retention in vivo. The quantitative (124)I-mIBG PET/CT is a promising new tool to predict tumor radiation doses with (131)I-mIBG therapy of neuroblastoma. This methodology may be applied to tumor dosimetry of (131)I-mIBG therapy in human subjects using (124)I-mIBG pretherapy PET/CT data.